Efektivitas Variasi Dosis Resin dalam Menurunkan Kesadahan Air Sumur Gali di Perumahan Griya Citra Asri, Temuwuh Kidul, Balecatur, Gamping, Sleman, Yogyakarta Tahun 12 - Afifah Nurlaila Desi Wijayanti; Purwanto Purwanto; Mohamad Mirza Fauzie (Poltekkes Kemenkes Yogyakarta, 2012)
The continuous use of hard water can cause health disorders as well as economic, aesthetic, and technical problems. According to the regulation issued by the Ministry of Health No. 416/Menkes/Per/IX/1990 about the quality requirements for clean water, the maximum levels permitted for water hardness parameter is 500 mg/l. Based on the preliminary study conducted at Griya Citra Asri Housing in Temuwuh Kidul, Balecatur, Gamping, Sleman, it was found that the water hardness of the dug well water had exceeded the threshold, i.e. 753,33 mg/l as CaCO3. This study was aimed to determine the effect of various doses of resin in decreasing the water hardness of the housing’s well water by performing a true experiment with pre-test post-test with control group design and following a simple random sampling method. The results showed that the average reduction of water hardness were 33,61%, 39,80%, 50.,89%, 60,27%, and 74,48% for resin doses of 15 mg/l, 20 mg/l, 25 mg/l, 30 mg/l and 35 mg/l respectively. The one way anova statistical test proved that the difference were significant (p<0,05) and it could be concluded that 20 mg/l was the most effective dose.